Investigation of reinforced foam waste with natural or synthetic fibers - Abdel Mohsen, Riham (AUC Knowledge Fountain, 2014)
The production of plastics has reached about 300 million tons globally each year. The use of energy resources, the health problem and the impacts on the environment from its disposal phase trigger overriding concerns on plastic recycling which can both save energy consumption in production phase and achieve green end-of-life approach for plastics. Polystyrene is hardly biodegradable. It takes at least 500 years to decompose. It is estimated that by volume, it takes as much as thirty percent of landfills worldwide. It is also flammable subject to risk of accidental ignition and cause of huge fires. Polystyrene is not recycled because it is usually not cost effective. The problems with recycling polystyrene are economical and technical. The start-up costs for a polystyrene recycling plant are enormous and the pay-off, as of now, is not cost effective. The main objective of the thesis is to develop a new recycling technology in order to produce a cost effective product entirely out of waste. Polystyrene waste is reinforced with fibers whether natural or synthetic to improve its mechanical properties and hence could be used for different useful applications. The new products will reduce the detrimental problem of solid waste to the environment as well as save energy, natural resources and cost. Finally, an innovative, environment friendly, cheap and effective yet simple technology is developed to determine the suitability of polystyrene foam waste fiber reinforced composites techniques Mechanical properties of plastic composites using polystyrene foam waste reinforced with synthetic fibers such as fiber glass waste, or natural fibers such as rice straw have been investigated in this study. The fiber waste (synthetic, or natural) was mixed with the polystyrene waste at four weight ratios of 20,30,40, and 50% for the experiments. Samples were prepared using indirect heating and hydraulic press then mechanical properties were evaluated including tensile, flexural, compression and abrasion. The obtained results indicated that the mechanical properties of the synthetic fiber composites were higher than the natural fiber reinforced composites. The best synthetic fiber content was 30 wt.%. The tensile strength was increased by 102 % , the flexural by 54 % , the compression strength by 19 % and abrasion wear better than the properties of the polystyrene waste without reinforcement.